Feedback uzyskiwany drogą elektroniczną - Ewa Półtorak, Ewa Półtorak (Neofilolog, 2019)
The use of Information and Communication Technologies (ICT) in the foreign language learning-teaching process has made traditional methods of obtaining feedback more sophisticated as, nowadays, it is possible to get feedback electronically. The paper is concerned with methods of getting feedback by means of selected computer and Internet tools that support the foreign language learning-teaching process. A range of these tools are analyzed and discussed from the perspective of their usefulness for both the teacher and student.